2018
DOI: 10.1111/epi.14047
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal seizure detection: A review

Abstract: Summary A review is given on the combined use of multiple modalities in non electroencephalography (EEG)‐based detection of motor seizures in children and adults. A literature search of papers was done on multimodal seizure detection with extraction of data on type of modalities, study design and algorithm, sensitivity, false detection rate, and seizure types. Evidence of superiority was sought for using multiple instead of single modalities. Seven papers were found from 2010 to 2017, mostly using contact sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 26 publications
0
55
0
1
Order By: Relevance
“…These devices and their effectiveness are discussed in detail in other articles from this supplement. 12,51,52 Some evidence suggests that nocturnal supervision reduces the risk of SUDEP, 42,53 indirectly supporting the view that timely postictal intervention by a caregiver could counteract some of the mechanisms at stake in SUDEP, such as the prone position. Other indirect arguments pointing to the same conclusion have been derived from epilepsy monitoring unit (EMU) data.…”
Section: Warning Of An Ongoing Seizurementioning
confidence: 97%
See 1 more Smart Citation
“…These devices and their effectiveness are discussed in detail in other articles from this supplement. 12,51,52 Some evidence suggests that nocturnal supervision reduces the risk of SUDEP, 42,53 indirectly supporting the view that timely postictal intervention by a caregiver could counteract some of the mechanisms at stake in SUDEP, such as the prone position. Other indirect arguments pointing to the same conclusion have been derived from epilepsy monitoring unit (EMU) data.…”
Section: Warning Of An Ongoing Seizurementioning
confidence: 97%
“…Several commercially available wearable devices are providing reliable detection of GTCS with an associated alarm that can prompt immediate intervention from surrounding relatives or caregivers. These devices and their effectiveness are discussed in detail in other articles from this supplement …”
Section: Warning Of An Ongoing Seizurementioning
confidence: 99%
“…Although the small‐scale studies reported an improved performance in the multimodal setting as compared to the unimodal one, the sensitivity and FAR of these multimodal TCS detectors was not superior to what the 2 large‐scale multicenter studies reported on the unimodal, EMG‐based devices. For a detailed review on multimodal seizure detection, the reader is referred to another paper of this supplement of Epilepsia …”
Section: Emg‐based Automated Detection Of Convulsive Seizuresmentioning
confidence: 99%
“…For a detailed review on multimodal seizure detection, the reader is referred to another paper of this supplement of Epilepsia. 33 We have found 2 patents corresponding to the commercially available EMG-based seizure-detection devices. 34,35 Our PubMed search identified 4 prospective studies on clinical validation of accelerometry-based, wearable devices using real-time detection of TCS.…”
Section: Detection Of Convulsive Seizuresmentioning
confidence: 99%
“…Conversely, 2 other field studies with high sensitivity are reported in this supplement: one using accelerometry showed a median sensitivity of 90% and a false alarm rate of only 0.1/d for GTCS detection, whereas another one using video‐only in a residential care setting reported 100% sensitivity and a median false alarm rate of 0.78 per night . Multimodal seizure detection is currently characterized by various sensing methods and highly variable sensitivity (4%‐100%) and rate of false alarms (0.25‐20 per 8 hours) …”
mentioning
confidence: 94%